Chemical genetics strategy identifies an HCV NS5A inhibitor with a potent clinical effect - Gao, Min; Nettles, Richard E.; Belema, Makonen; Snyder, Lawrence B.; Nguyen, Van N.; Fridell, Robert A.; Serrano-Wu, Michael H.; Langley, David R.; Sun, Jin-Hua; O’Boyle II, Donald R.; Lemm, Julie A.; Wang, Chunfu; et al. (Nature (London), 2010)
New drugs for hepatitis C The development of direct-acting antiviral agents to treat chronic hepatitis C virus (HCV) infection, much needed clinically, has focused largely on inhibitors of two viral enzymes, the protease NS3 and NS5B, an RNA-dependent RNA polymerase essential for HCV replication. BMS-790052, identified using chemical genetics as a powerful specific HCV inhibitor, is a small-molecule inhibitor of a third viral molecule that has no known enzyme activity, the non-structural protein 5A (NS5A). A research team from Bristol-Myers Squibb this week reports on the discovery and virological profile of BMS-790052 and discloses clinical trial observations with this compound in normal healthy volunteers and HCV-infected subjects. These results establish proof-of-concept for HCV NS5A inhibition as a clinically relevant mechanism. In vitro data point to synergistic interactions with known HCV inhibitors, suggesting that cocktails of antiviral agents may be a viable therapeutic approach. Almost 200 million people worldwide are chronically infected with hepatitis C virus. Current treatments are poorly tolerated and not wholly effective, so new drugs are needed. Here, a potent new inhibitor of hepatitis C virus is described. This inhibitor targets the viral protein NS5A, and shows potential as part of a therapeutic regimen based on a combination of viral inhibitors. The worldwide prevalence of chronic hepatitis C virus (HCV) infection is estimated to be approaching 200 million people 1 . Current therapy relies upon a combination of pegylated interferon-α and ribavirin, a poorly tolerated regimen typically associated with less than 50% sustained virological response rate in those infected with genotype 1 virus 2 , 3 . The development of direct-acting antiviral agents to treat HCV has focused predominantly on inhibitors of the viral enzymes NS3 protease and the RNA-dependent RNA polymerase NS5B 4 . Here we describe the profile of BMS-790052, a small molecule inhibitor of the HCV NS5A protein that exhibits picomolar half-maximum effective concentrations (EC 50 ) towards replicons expressing a broad range of HCV genotypes and the JFH-1 genotype 2a infectious virus in cell culture. In a phase I clinical trial in patients chronically infected with HCV, administration of a single 100-mg dose of BMS-790052 was associated with a 3.3 log 10 reduction in mean viral load measured 24 h post-dose that was sustained for an additional 120 h in two patients infected with genotype 1b virus. Genotypic analysis of samples taken at baseline, 24 and 144 h post-dose revealed that the major HCV variants observed had substitutions at amino-acid positions identified using the in vitro replicon system. These results provide the first clinical validation of an inhibitor of HCV NS5A, a protein with no known enzymatic function, as an approach to the suppression of virus replication that offers potential as part of a therapeutic regimen based on combinations of HCV inhibitors.